Trilha da inovação : uma abordagem aplicada a Micro e Pequena Empresa (MPE) - Gonçalves, Debora Simony Leventi Aleixes (2020)
Micro and Small Companies (MPEs), classified here according to billing as provided for in the country's federal legislation, according to a survey by SEBRAE in 2016, participate in 99% of the total companies in the country, generating more than five million jobs of formal jobs, however, 56% of managers of MSEs have low education and more than 24% of companies open in the year die before the first twenty-four months. Some MSEs have difficulties in creating and maintaining creative processes that favor innovation, the creation of innovative teams and spaces, and neither do they manage innovation, be it creation, implantation, maintenance and development. These difficulties lead us to think about how to develop a path that provides information, tools and presents actors that can help in the transfer of technology, knowledge and knowledge, bringing the theme of innovation as the central axis of the company. In this context, the general objective of this work was to produce a Strategic Innovation Trail (TEI) with the purpose of presenting, visually to entrepreneurs from Micro and Small Enterprises (MPEs), the innovation ecosystem of Mato Grosso, its actors, projects focused on basic / advanced research and the provision of services for innovation, the lines of financing, processes and tools whose training can guide the management of innovation in the business environment. In methodological terms, the work was characterized as an applied research, with an exploratory objective, using the qualitative analysis approach, in which the relationship between reality and the object of study was verified, obtaining several characteristic interpretations of a research carried out in different phases, from data collection through bibliographic research and opinion polling (survey) with specialists and businessmen, to the modeling of the trail with a prototyping workshop in an MPE in Cuiabá / MT and, finally, discussion results and track evaluation. The main result obtained in the work was the Innovation Strategy Trail (TEI) composed of the Mato Grosso Innovation Ecosystem pillars, Basic and Applied Research, Service Provision for Innovation, Sources of Promotion and Financing, and Training, available via the website, which was evaluated positively by experts and businessmen. Other results obtained, considering the prototyping of the trail in a micro company, were the elaboration of the company's strategic planning, the incremental innovation in products offered and the authorial registration of new services by the company. It is expected that the Strategic Innovation Trail (TEI) contributes to the capacity for innovation, enhancing competitive advantage, improving management and reducing costs, generating profit and the sustainability of SMEs.